Troxerutin is a novel osmotic agent for peritoneal dialysis with protective cardiovascular actions - Kopytina, Valeria; Marchant, Vanessa; Rodrigues-Diez, Raquel; Pascual-Antón, Lucía; Toggweiler, Nora; Strahl, Lisa; Kane, Jamie; Tejera-Muñoz, Antonio; Cortés, Marcelino; Sucunza, David; Vaquero, Juan J; Vervloet, Marc; et al. (Nephrology, dialysis, transplantation, 2025)
End-stage renal disease patients require peritoneal dialysis (PD) as a life-saving therapy; however, they continue to experience systemic inflammation and increased cardiovascular pathology. These complications can be exacerbated by exposure to PD solutions (PDS) containing glucose. This highlights the clinical unmet need for novel osmotic agents to replace glucose. Here, we tested troxerutin, an FDA-approved drug, as a potential osmotic agent. To evaluate troxerutin osmotic and non-toxic effects, in vitro and in vivo experiments were done using artificial membranes, mice and cultured human mesothelial cells (MCs). The local and systemic consequences of chronic peritoneal exposure to PDS associated to renal insufficiency were investigated in a preclinical model. 5/6 nephrectomized C57BL/6 J mice were daily exposed to glucose- or troxerutin-PDS for 60 days, then evaluating tissue damage, proinflammatory markers, and cardiac damage. In vitro and in vivo studies revealed that troxerutin exhibits similar osmotic and ultrafiltration capacities to glucose, but with colloidal properties. Moreover, only glucose, but not troxerutin, reduced MC viability, induced mesothelial-to-mesenchymal transition, and increased damage markers (such as IL-6 and VEGF-A). In the preclinical model, long-term treatment with glucose-PDS, but not troxerutin-PDS, significantly increased peritoneal membrane thickening, tissue proinflammatory markers (evaluated in peritoneum, kidney, heart, and aorta) and cardiovascular damage (cardiac hypertrophy and fibrosis) in mice. These preclinical data clearly demonstrate the wide deleterious effects of chronic peritoneal exposure to glucose-containing PDS in mice with kidney insufficiency and that the replacement of glucose with troxerutin notably reduces these effects. Troxerutin emerges as a more biocompatible alternative to glucose as an osmotic agent for PD therapy, exhibiting no adverse local or systemic side effects in preclinical studies. This research presents a novel approach to reduce cardiovascular complications of PD in end-stage kidney disease.